Pengaruh Intellectual Capital Dan Mekanisme Corporate Governance Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2015-2017 - Khairuni, Rizka; Zahara; Santi, Elfitri (Jurusan Akuntansi Politeknik Negeri Padang, 2019)
The purpose of this research is to find out the influence of intellectual capital and corporate governance mechanism to the financial performance. The independent variables are intellectual capital and corporate governance mechanism. Corporate governance mechanism in this research is measured by indicators which consist of institutional ownership, managerial ownership, the board of independent comissioner, and the board of director. The dependent variables is the financial performance which is measured by return on assets (ROA). The samples are 64 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2015-2017 periods were have been selected by using purposive sampling. Data analysis method in this research is multiple linear regressions analysis with the SPSS 20th version application. The result of this research showed that partially, intellectual capital has positive influence to the financial performance. Meanwhile, corporate governance mechanism does not have any influence to the financial performance. Simultaneously, intellectual capital and corporate governance mechanism have positive influence to the financial performance.